2017
DOI: 10.26682/sjuod.2017.20.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study With Using Anfis to Evaluate the Performance of a Modified Closed Wet Cooling Tower

Abstract: The present study involves experimental and computational analysis to investigate the thermal performance of modified closed wet cooling tower in perspective of first and second law of thermodynamics (analysis of energy and exergy) according to Iraqi weather. The experimental study includes design, manufacture and testing prototype of a modified counter flow forced draft closed wet cooling tower. The modification based on addition packing to the conventional closed wet cooling tower. To assess the thermal perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Nasr et al developed a rapid design algorithm for evaporative coolers with plain tubes [22] and twisted tubes [23], giving the relationship between the heat transfer coefficient, pressure drop, heat transfer area, and mass transfer coefficient. Mahdi and Jaffal [24,25] carried out an exergy analysis on an evaporative cooler and found that the exergy loss is directly proportional to the air flow rate, the water flow rate in the pipe, the water inlet temperature in the pipe, and the wet bulb temperature at the air inlet, and inversely proportional to the spray water flow. The correlation equation of the heat and mass transfer coefficients was established.…”
Section: Introductionmentioning
confidence: 99%
“…Nasr et al developed a rapid design algorithm for evaporative coolers with plain tubes [22] and twisted tubes [23], giving the relationship between the heat transfer coefficient, pressure drop, heat transfer area, and mass transfer coefficient. Mahdi and Jaffal [24,25] carried out an exergy analysis on an evaporative cooler and found that the exergy loss is directly proportional to the air flow rate, the water flow rate in the pipe, the water inlet temperature in the pipe, and the wet bulb temperature at the air inlet, and inversely proportional to the spray water flow. The correlation equation of the heat and mass transfer coefficients was established.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling tower is a heat exchanger to reduce water temperature when small amount is evaporated to the ambient air when they become in direct contact with each other. Cooling tower is complement to the power generation units, nuclear reactor, chemical and petrochemical industry, and air conditioning plants [1]. To improve the efficiency of these systems the researchers and designers focus on developing the thermal performance of the cooling tower because of their great influence to increase the efficiency of these mentioned systems [2].…”
Section: Introductionmentioning
confidence: 99%